Antigen-Specific T Cell Analysis Reveals That Active Immune Responses to β Cell Antigens Are Focused on a Unique Set of Epitopes - Yang, Junbao; Wen, Xiaomin; Xu, Hengyu; Torres-Chinn, Nadia; Speake, Cate; Greenbaum, Carla J; Nepom, Gerald T; Kwok, William W (The Journal of immunology (1950), 2017)
CD38 is an activation marker that is present on recently activated T cells, but absent on resting memory T cells. In this study, we show that CD45RO+CD38+ β cell Ag-specific CD4+ T cells were present at higher frequencies in type 1 diabetes subjects compared with those in healthy subjects. These results imply an ongoing β cell immunity years after onset of diabetes and suggest these activated T cells have an active role in the disease process. The Ag specificities of these activated T cells were determined by a novel CD154 T cell epitope mapping assay. Although each patient usually had a unique set of epitopes recognized by these T cells, two epitopes, DR0401-restricted modified preproinsulin peptide 78–90K88S and zinc transport 8 266–285, were repeatedly identified in multiple subjects. Identifying these T cells and their specific antigenic epitopes might provide immunotherapeutic targets for personalized therapies.